Intelligent Flight Control System Design for the Small UAV Based on the Adaptive Neuro-Fuzzy Inference System - Komnatska, M.M.; Bondarenko, D.P. (Управляющие системы и машины, 2017)
The paper considers a problem of flight control system design for small unmanned aerial vehicle with elements of intelligent control. The design procedure is illustrated by an example of unmanned aerial vehicle longitudinal control with application of adaptive neurofuzzy inference model.